IMPROVING TEACHERS’ PEDAGOGICAL SKILLS (Conference Zone, 2022)
The learning process is a memorable part of both teachers' and students' lives. Regardless of the field, all those who have gained professionalism will be taught as teachers first. As a result, one of the most serious challenges today is the training of outstanding and excellent employees in the field of pedagogy. The author of this article goes into great detail about how pedagogical and psychological opportunities are formed during the teacher training process